Contextual determinants of HR professionals’ self-perceptions of unethical HRM practices - Simões, E.; Duarte, A. P.; Neves, J.; Silva, V. H. (European Journal of Management and Business Economics, 2019)
This study examined human resources (HR) professionals’ self-perceptions of ethically questionable human resource management (HRM) practices (i.e., a disregard for the individual, favoring those in power, and discrimination). The research sought specifically to determine how these perceptions are influenced by their organizations’ ethical infrastructure and corporate social responsibility (CSR) practices. Data were collected from 134 HR professionals using an anonymous structured questionnaire. The scope of organizations’ ethics programs and the degree of importance given to developing an ethical infrastructure were found to predict the level of acceptance of unethical HRM practices related to discrimination. These practices are also less acceptable to professionals from organizations that are perceived as more socially responsible regarding their employees. Additional studies with larger samples are needed to determine more clearly not only the influence of contextual determinants but also the practical consequences of high levels of acceptance of unethical practices in HRM. Organizations can decrease their HR professionals’ acceptance of ethically questionable HRM practices by developing and emphasizing a strong ethical infrastructure and CSR practices, especially those affecting employees. HR professionals’ perceptions of ethical issues have rarely been analyzed using empirically tested methods. By surveying HR professionals, this study contributes to a fuller understanding of their perceptions regarding the ethics of their own practices. The results show that contextual determinants play an important role in predicting the level of acceptance of unethical HRM practices, especially those leading to discrimination.